2020
DOI: 10.1080/07399332.2020.1832097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spirituality on resilience and coping during the COVID-19 crisis: A mixed-method approach investigating the impact on women 

Abstract: Spirituality has been known to have a positive correlation to resilience during disasters. This study investigated the impact of spirituality on resilience during our current pandemic. A mixed-method approach was used to analyze correlations between spirituality and resilience of women. Correlations were noted to be statistically significant with Pearson's correlation of -.450 at 0.001, CD-RISC (M ¼ 77.94), and DSES (M ¼ 39.74). Thematic analysis of six open-ended questions provide depth to quantitative findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
3
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 55 publications
7
57
3
9
Order By: Relevance
“…Other women reported that they were grateful for little things in their lives and the opportunity to slow down and spend more time doing joyful activities. Some women explained how they maintained their gratitude, for example, by keeping a gratitude journal and by downward social comparison thinking the situation could be worse (Roberto et al, 2020). These findings highlight that, for some, faith may promote resilience and mental health, especially during crises.…”
Section: Mature Gratitude and Covid-19 Threatsmentioning
confidence: 90%
“…Other women reported that they were grateful for little things in their lives and the opportunity to slow down and spend more time doing joyful activities. Some women explained how they maintained their gratitude, for example, by keeping a gratitude journal and by downward social comparison thinking the situation could be worse (Roberto et al, 2020). These findings highlight that, for some, faith may promote resilience and mental health, especially during crises.…”
Section: Mature Gratitude and Covid-19 Threatsmentioning
confidence: 90%
“…Previous studies have proved the effect of spiritual well-being on resilience (Legada, Madrigal and Maravilla, 2020;Duran, Avcı and Esim, 2020) However, there are only a few studies confirming this relationship during COVID-19 pandemic. Among these scarce studies, Roberto et al (2020) also examined spirituality-resilience during relationship during COVID-19 and their qualitative study revealed the impact of spirituality on resilience in the context of the COVID-19. Similarly, Maraj, Gülerce, Rana and Meraj (2020) explored the relationship between resilience and hopelessness and showed the mediator role of spirituality in this relationship.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, spiritual perspectives contribute to better tolerance to stress, and a better ability to cope with serious diseases and social isolation (Sharma et al, 2017). According to Roberto et al (2020) religion and spirituality are important factors that make individuals reframe the crisis and perceive event more positively. Individuals having connectedness with their environment and with their inner world are better at finding solutions to their problems and they are better at making sense of events (Narcikara, 2017).…”
Section: Effect Of Spirituality On Resilience During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, el discurso de los entrevistados frecuentemente posee elementos asociados a la resiliencia, puntualmente de origen espiritual. Tal hallazgo es congruente con un estudio reciente en el que se encontró una relación estadísticamente significativa entre espiritualidad y resiliencia durante la pandemia de COVID-19 (Roberto, Sellon, Cherry, Hunter-Jones, & Winslow, 2020).…”
Section: Discussionunclassified